THE UTILIZING OF ZEOLITE MINERALS AS AGRICULTURE SOIL CONDITIONER IN RELATION TO ITS STANDARIZATION AND INCREASING FOOD CROP - M. Al-Jabri (Institut Teknologi Bandung, 2010)
The used of zeolite mineral as soil ameliorant on agricultural had been known since long time ago. Cation exchange capacity (CEC) of zeolite is â‰¥ 100 cmol(+) kg-1 which regulated on SNI No 13-3494 1994 is a determining quality of zeolite test. However, it is very reasonable to be revised. There are several reason why determining CEC of zeolite on SNI No 13- 3494-1994 must to be revised, because there is an error as possible as on determining CEC of soil. The research aimed to study the measurement of CEC zeolite for agricultural which conducted on five laboratories were (1) Bogor Agricultural University by using stirring (shaking)-sentrifusi decantation methods, (2) Service Soil Laboratory at Indonesian Soil Research Institute by using percolation method that measured by calorimetric auto analyzer, (3) Soil Laboratory at Indonesian Soil Research Institute by using percolation method that measured by spectrometry, (4) PT. Sucofindo, and (5) Research and Development Centre for Mineral and Coal Technology by using percolation method. The result from quality test of CEC zeolite A and zeolite B from five laboratories was significant different, because the difference procedures of the method such as zeolite quality (grade and types), zeolite fineness, and ratio of zeolite to ammonium acetate solution. The criteria of CEC zeolite for agricultural on SNI recommended to be revised on five types are (1) â‰¥ 100 cmol(+) kg-1(class A); 100 - 80 cmol(+) kg-1 (class B); 80